Peripheral-Arterial Tonometry for Assessing Endothelial Function in Relation to Dietary Habits. (June 2013) - Cioni, Gabriele; Boddi, Maria; Fatini, Cinzia; Romagnuolo, Ilaria; Casini, Alessandro; Gensini, Gian Franco; Abbate, Rosanna; Sofi, Francesco
Background: Peripheral-arterial tonometry (PAT) provides, with good reproducibility, measures of nitric oxide–mediated endothelial response, which correlate with flow-mediated dilation (FMD) findings obtained by brachial artery ultrasound. Few data about the ability of exploring endothelial function by PAT in relation to dietary habits are available. The aim of this study was to evaluate natural logarithm of reactive hyperemia index (lnRHI) in subjects referred for primary prevention, in relation to classic risk factors, in particular to adherence to Mediterranean diet and red wine consumption. Methods: The study population was composed of 95 consecutive clinically stable subjects in primary prevention for cardiovascular diseases. All subjects underwent medical questionnaire, clinical examination, and PAT for endothelial function evaluation. Results: A significant inverse correlation between lnRHI values and body mass index ( r = −0.284; P = 0.022) was found. We described a gradual reduction in lnRHI values, corresponding to the increase in the number of risk factors (0.75 [0.31–1.26], 0.66 [0.25–0.97], 0.63 [0.37–1.19], 0.48 [0.32–0.71], 0.43 [0.31–0.91], respectively, for none, 1, 2, 3, and 4 cardiovascular risk factors; P = 0.004). A significant positive correlation between score of adherence to Mediterranean diet and lnRHI values was found ( r = 0.307; P = 0.002). Higher adherence to Mediterranean diet was found in subjects with lnRHI values greater than 0.40 in comparison to others (39 [27–50] vs 33 [28–45], respectively; P = 0.064). The lnRHI values were significantly higher in regular drinkers in comparison to nonregular drinkers (0.46 [0.25–0.83] vs 0.70 [0.32–1.26], respectively; P < 0.0001). Relationship between reactive hyperemia index and red wine consumption remained statistically significant even after adjustment for age, sex, body mass index, smoking habit, hypertension, and adherence to Mediterranean diet. Conclusions: Our findings strengthen the ability of PAT to evaluate alterations of endothelium response to ischemia, in relation to physiological and clinical conditions, so indicating possible usefulness to optimize and personalize risk stratification.